Perancangan Sistem Informasi Pendaftaran Magang Berbasis Web Menggunakan Framework Laravel Pada Diskominfo Binjai - Muhammad Abdillah Syam; Aninda Muliani Harahap; Fahmi Aditya Abdi; Siddik Tambak (Cattleya Darmaya Fortuna, 2026)
Internship registration at the Communication and Information Technology Office of Binjai City still uses a conventional system that requires prospective participants to attend in person, submit physical documents, and rely on informal communication through WhatsApp. This condition causes administrative process inefficiency, limited service accessibility, dependency on personal connections, risk of document loss, and minimal transparency in the registration process. This research aims to design a web-based internship registration information system to improve administrative process efficiency and public service quality at Diskominfo Binjai City. The development method used is Waterfall with stages of requirements analysis, system design, implementation, testing, and maintenance. The system is built using the Laravel framework with Model-View-Controller (MVC) architecture, PHP programming language, as well as Bootstrap and jQuery for the user interface. System design uses Use Case Diagrams, Activity Diagrams, and Entity Relationship Diagrams (ERD) to model functional requirements and database structure. Research results show the system successfully transforms the registration process from manual to digital with features including online registration, administrator dashboard, applicant data management, automatic notification system, and contact message management. System implementation improves operational efficiency through process automation, eliminates geographical and temporal barriers, removes dependency on personal connections, and enhances public service transparency and accountability through standardized procedures and structured digital documentation. This system contributes significantly to modernizing government governance and improving public service quality at the local level.